Productivity of Sargassum linearifolium in potassium fortified inland saline water under laboratory conditions - Bui, H.; Luu, T.; Fotedar, Ravi; Tantulo, U. (Wiley-Blackwell Publishing Ltd., 2017)
Growing aquatic species in inland saline water (ISW) is one way to reduce the adverse impact of ISW to agriculture farms. This 84-day laboratory-trial was conducted to study the growth of Sargassum linearifolium cultured in ocean water (OW), ISW, ISW fortified with potassium equivalent to 100% (ISW100), 66% (ISW66) and 33% (ISW33) of potassium in OW at 35 g/L. The biomass and cumulative specific growth rate (SGR) of S. linearifolium increased significantly (p < .05) with increased potassium in ISW until 56 days and then declined. The ISW100 and OW resulted in similar growth patterns and yielded peak biomass at day 42, proving static biomass for the next 28 days before declining. The biomass of S. linearifolium cultured in ISW and ISW33 significantly (p < .05) decreased and was lower than in ISW100 and died after day 56. The SGR of S. linearifolium in OW, ISW100 and ISW66 levelled off and showed no difference during the first 56 days. The S. linearifolium biomass and SGR negatively and significantly (p < .05) correlated with the concentrations of nitrate, phosphate in all waters. The increased potassium concentration in ISW similar to its concentration in SW brought the growth of S. linearifolium cultured to a level that was similar in OW.